Knowledge-Based Decision Support for Integrated Water Resources Management with an application for Wadi Shueib, Jordan - Riepl, David (KIT Scientific Publishing, 2013)
This book takes a two-staged approach to contribute to the contemporary Integrated Water Resources Management (IWRM) research. First it investigates sub-basin-scale IWRM modelling and scenario planning. The Jordanian Wadi Shueib is used as exemplary case study. Then, it develops a framework to collaboratively manage planning and decision making knowledge on the basis of semantic web technologies. Future IWRM initiatives can benefit from the valuable insights achieved in the presented study.